2005
DOI: 10.1111/j.1525-1470.2005.22203.x
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of Atopic Eczema in Children after Heart Transplantation in the First Year of Life

Abstract: Children undergoing heart transplantation in the first year of life appear in clinical observation to develop atopic eczema at an above-chance frequency despite immunosuppressive therapy with cyclosporine A. A clinical study was undertaken to clarify the extent to which those children develop atopic eczema with above-chance frequency. In this cross-sectional study, we examined 41 consecutive children after heart transplantation. Twenty-seven underwent heart transplantation in the first year of life, seven afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
5
2
Order By: Relevance
“…Although observational and highly speculative, we suggest that CsA treatment may be related to this rebound phenomenon with increasing serum IgE levels that was observed in a subpopulation of AD patients. The literature suggests a role for CsA in this phenomenon 11–13 . Surprisingly, our results are, in this aspect, in contrast to previous studies, which have been reviewed by Naeyaert et al 14 .…”
Section: Discussioncontrasting
confidence: 99%
“…Although observational and highly speculative, we suggest that CsA treatment may be related to this rebound phenomenon with increasing serum IgE levels that was observed in a subpopulation of AD patients. The literature suggests a role for CsA in this phenomenon 11–13 . Surprisingly, our results are, in this aspect, in contrast to previous studies, which have been reviewed by Naeyaert et al 14 .…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports, although limited, have observed that allergies are common among pediatric heart recipients, 16,17 and our results confirm that observation. An elevated eosinophil count was associated with allergic conditions and allergic conditions were associated with transplant at a younger age; however, allergic conditions and younger age at transplant were not associated with freedom from rejection in our analysis.…”
Section: Discussionsupporting
confidence: 95%
“…10,11 The balance between Th1 and Th2 phenotypes may be important in mediating allograft rejection vs acceptance. 9,12 Allergic conditions are more prevalent in pediatric transplant recipients, [13][14][15][16][17] and the peripheral eosinophil count is a marker of allergic conditions. Given the possible role of Th1 vs Th2 in rejection vs allergic responses, we sought to identify potential clinical markers of an underlying Th2 dominance and immunologic quiescence by examining the association between the longitudinal eosinophil count and the presence of allergic conditions with rejection history in a pediatric heart transplant cohort.…”
mentioning
confidence: 99%
“…Selective inhibition of the Th1 response likely shifts the immune response toward the Th2 pathway, predisposing transplant patients to the development or worsening of AD (Ponte et al, ; Weimer et al, ). Similar to immunosuppression, thymectomy at or around the time of HXT has been employed as a method toward the prevention of organ rejection, but it has been shown to accelerate premature aging of the immune system, leading to reduced TCR diversity, which is associated with AD (López‐Abente et al, ; Niemeier et al, ; Ponte et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that children who received heart transplants (HXT) and subsequent thymectomies before their first birthday had an increased risk of developing AD in conjunction with immunosuppression (Niemeier et al, ). In this study, 9/11 children (82%) with HXT performed before their first birthday developed AD, believed to be due to premature immune maturation selectively inhibiting the Th1 > Th2 inflammatory response (Niemeier et al, ; Shaw, Currie, Koudelka, & Simpson, ). Here, we report the case of a young immunosuppressed heart transplant patient with severe AD successfully treated with dupilumab (Dupixent, Regeneron, and Sanofi).…”
Section: Introductionmentioning
confidence: 99%